Mine Detecting Robot with Multi Sensors Controlled Using HC-12 Module - Kirubakaran.S.J, Jebasingh; kumar jha, Anish; kumar, Dheeraj; Poornachandran Prakash, Sadambi (International Journal of Engineering and Technology, 2018)
Application of robot for person safekeeping is an important aspect in the explore province. From medical to military use several functions are residential to fructify person life. A mine detecting robot is a wide military progression and a lifesaving design that can benefit humankind. The robot is guided by HC-12Â module that allows it to scan the testing area within 1.8km and metal detector is used as mine detecting sensor placed in front of the vehicle, while GPS is used to provide the exact location of the infected area. This paper put forward to design of a mine detecting sensor using HC-12 and GPS while applying it in a robotic sample. The embedded proposed system is based on Arduino technologies and guided by an HC -12 Module.Â Â